Equivalent weight loss for weight management programs delivered by phone and clinic. (25th May 2013) - Donnelly, Joseph E.; Goetz, Jeannine; Gibson, Cheryl; Sullivan, Debra K.; Lee, Robert; Smith, Bryan K.; Lambourne, Kate; Mayo, Matthew S.; Hunt, Suzanne; Lee, Jae Hoon; Honas, Jeffrey J.; Washburn, Richard A.
<x xml:space="preserve">Abstract</x> Objective Face‐to‐face (FTF) weight management is costly and presents barriers for individuals seeking treatment; thus, alternate delivery systems are needed. The objective of this study was to compare weight management delivered by FTF clinic or group conference calls (phone). Design and Methods Randomized equivalency trial in 295 overweight/obese men/women (BMI = 35.1±4.9, Age = 43.8±10.2, Minority = 39.8%). Weight loss (0‐6 months) was achieved by reducing energy intake between 1, 200 and 1, 500 kcal/day and progressing physical activity (PA) to 300 min/week. Weight maintenance (7‐18 months) provided adequate energy to maintain weight and continued 300 min/week of PA. Behavioral weight management strategies were delivered weekly for 6 months and gradually reduced during 7‐18 months. A cost analysis provided a comparison of expenses between groups. Results Weight change from baseline to 6 months was −13.4 ± 6.7% and −12.3 ± 7.0% for FTF clinic and phone, respectively. Weight change from 6‐18 months was 6.4 ± 7.0% and 6.4 ± 5.2%, for FTF clinic and phone, respectively. The cost to FTF participants was 789.58 more per person. Conclusions Phone delivery provided equivalent weight loss and maintenance and reduced program cost. Ubiquitous access to phones provides a vast reach for this approach.